Pericyte: Potential Target for Hemorrhagic Stroke Prevention and Treatment - Li, Qiang; Liu, Xin; Ruan, Huaizhen; Chen, Yujie; Feng, Hua (Current Drug Delivery, 2017)
Background: Despite long-standing and worldwide efforts, hemorrhagic stroke remains a critical clinical syndrome that exerts a heavy toll on affected individuals and their families due to the lack of preventive and therapeutic targets. Objective: To clarify the pathogenesis of hemorrhagic stroke and to identify novel therapeutic targets. Method: Targeting pericytes, the typical mural cells of microvessels, could serve as a way to modulate microvascular permeability, development, and maturation by regulating endothelial cell functions and modulating tissue fibrosis and inflammatory responses. Results: Pericytes in hemorrhagic stroke may exert the following functions: before bleeding, the morphological aberration and dysfunction of pericytes may lead to aneurysm formation, angiopsathyrosis, and hemodynamic disturbances, ultimately causing vasculature rupture. In the acute phase after hemorrhage, pericytes are faced with a complicated bleeding environment, which results in the death of pericytes, blood-brain barrier damage, pericyte-mediated inflammatory cascades, white matter impairment, and ultimately aggravated neural injury. In the recovery period post-hemorrhage, in situ pericytes are activated and differentiate into neurons, glia and endothelial cells to repair the neural vascular network. Moreover, many pericytes are recruited to the lesion and contribute to blood-brain barrier remodeling, thus facilitating neurovascular functional recovery after stroke. Conclusion: Due to the multiple functions of pericytes in the development of vascular rupture and hemorrhagic stroke pathophysiology, additional drugs and trials targeting pericytes and evaluations of their effectiveness are required in future investigations to develop new strategies for the prevention and treatment of hemorrhagic stroke.
Keywords: prevention